2008
DOI: 10.1038/nphys883
|View full text |Cite
|
Sign up to set email alerts
|

Optical conductivity and the correlation strength of high-temperature copper-oxide superconductors

Abstract: Since their discovery in 1986, the high-temperature copper-oxide superconductors have been a central object of study in condensed-matter physics. Their highly unusual properties are widely (although not universally) believed to be a consequence of electron-electron interactions that are so strong that the traditional paradigms of condensed-matter physics do not apply: instead, entirely new concepts and techniques are required to describe the physics. In particular, the superconductivity is obtained by adding c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

23
135
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(159 citation statements)
references
References 19 publications
23
135
1
Order By: Relevance
“…Some screening is present within the one band Hubbard model, and it is important to see whether the full doping dependence of U could be understood on the basis of a more exact treatment of the Hubbard model -i.e., whether the physics of cuprates can be fully understood within a single-band Hubbard model. Clearly, as more correlations are added the doping dependence of the effective U systematically decreases from Hartree-Fock calculations 31 to the present QP-GW model, to recent DMFT calculations that can successfully describe the doping evolution of the cuprates with fixed-U models 27,40,41 . However, neither exact diagonalization nor QMC with fixed U = 8t capture the ASWT, Fig.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Some screening is present within the one band Hubbard model, and it is important to see whether the full doping dependence of U could be understood on the basis of a more exact treatment of the Hubbard model -i.e., whether the physics of cuprates can be fully understood within a single-band Hubbard model. Clearly, as more correlations are added the doping dependence of the effective U systematically decreases from Hartree-Fock calculations 31 to the present QP-GW model, to recent DMFT calculations that can successfully describe the doping evolution of the cuprates with fixed-U models 27,40,41 . However, neither exact diagonalization nor QMC with fixed U = 8t capture the ASWT, Fig.…”
Section: Discussionmentioning
confidence: 82%
“…At high energies, we subtract off a background from the experimental spectra associated with interband transitions to higher-lying bands not included in the present one band calculations. 16,[25][26][27][28] . We use a doping-independent background contribution shown as black dashed lines in Figs.…”
Section: Quantifying Anomalous Spectral Weight Transfermentioning
confidence: 99%
“…4 A noticeable case from the x-ray absorption spectroscopy (XAS) was proposed by Peets et al 5 By compiling available XAS data for different cuprates, the spectral weight of ZRS was claimed to be saturated for the hole doping level p ≥ 0.21. (Also, see an earlier statement of saturated ZRS weight with p > 0.16 in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recent theoretical and experimental advances have demonstrated that electronic correlations profoundly influence the optical response at energies up to several eV. [6,15,16,17,18,19]. Spectroscopic ellipsometry allows one to accurately detect such modifications and is hence a highly distinctive probe of electronic correlations in transition metal oxides [18,19].…”
mentioning
confidence: 99%
“…Spectroscopic ellipsometry allows one to accurately detect such modifications and is hence a highly distinctive probe of electronic correlations in transition metal oxides [18,19]. Dynamical mean-field theory (DMFT) calculations explain many aspects of strong temperature and doping dependent modifications of the optical spectral weight (SW) in the normal state of the superconducting cuprates [15,16,17]. Very recent DMFT studies indicate that LaFeAsO is slightly below the critical value of the Hubbard U required to obtain an insulating state [6,7].…”
mentioning
confidence: 99%